Drivers of tolerance in Post-Arab spring Egypt: Religious, economic, or government endorsements? - Hassan, Mazen; Shalaby, Marwa (Political Research Quarterly)
Previous work on political tolerance has overwhelmingly focused on established democracies. Consequently, our knowledge continues to be limited with regard to the drivers of tolerance in less democratic transitional and nondemocratic settings. In this paper, we examine what could best promote tolerance of least-favored political groups in such contexts. We use a survey experiment in Egypt to test competing theories through exposing respondents to different primes, emphasizing the importance of tolerance on the basis of religious, economic, or government endorsements. Respondents were then asked questions to gauge their tolerance levels toward their least-favored group. We control for the level of trust in government, religiosity, interpersonal trust, contact, and political knowledge. Our data show soaring levels of intolerance among Egyptians. However, we found evidence that priming respondents with the economic benefits of having a tolerant society is the most effective way to promote tolerant attitudes, especially among those with lower levels of education and younger age groups. Additionally, our analysis demonstrated that respondents$1 (Blevel of trust in government has a strong effect on tolerance attitudes. - Reproduced.s
Keywords: Political tolerance; Middle East - Egypt